Is quadrant biopsy adequate as first-line sampling scheme in men likely to have non-organ-confined prostate cancer - Brnić, Zoran (Radiology and oncology (Ljubljana), 2005)
Background. While extensive prostate biopsy (PB) in the patients with early prostate cancer (PC) provides better sensitivity and more precise tumour staging, in the patients with advanced PC, it is virtually only a confirmationof malignancy. The purpose of our study was to find out whether the quadrant prostate biopsy (QPB) provides a sufficient first-line pathological evaluation in the patients likely to have advanced PC, and whether the reduction of core number impairs the competence of PB through missing quantitative histology information. Methods. We studied 84 men who underwent PB and classified into groups Ha (highly ) and L (low likely to have advanced PC). Pathological results of 5-12 cores PB and simulated QPB were retrospectively compared, particularly for the presence of PC, tumour volume, Gleason score (GS), and the presence of htghgrade prostatic intraepithelial neoplasia (HGPIN). Results. The PC detection rate was not impaired in group H, but dropped significantly in group L, while the percentage of positive cores was insignificantly changed in group H (p=0.39), but significantly decreased in group L (p=0.04) due to the sampling scheme reduction. No HGPIN was missed with QBP in group H, while 2 HGPIN were missed in group L. Insignificant GS changes resulted in both groups as a consequence of the limitation to QPB. Conclusions. QPB is an appropriate first-line schemein the patients with advanced PC as the information lost due to the corenumber reduction is mainly not critical for patient management.
Keywords: biopsija; Biopsija igelna; Biopsy, Needle; diagnostika; Pathology; prostata; Prostata, novotvorbe; prostate; Prostate-Specific Antigen; Prostatic Neoplasms; Prostatični -specifični antigen; rak (medicina)